2023
DOI: 10.1002/bco2.280
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic urethral lift for subjects in urinary retention (PULSAR): 12‐Month results of a prospective controlled trial compared with real‐world outcomes

Mark Rochester,
Ruth Doherty,
Toby Page
et al.

Abstract: ObjectiveTo examine the safety and efficacy of prostatic urethral lift (PUL) in acute urinary retention (AUR) patients within a controlled (PULSAR) and real‐world setting (Real‐World Retrospective study).Materials and methodsPULSAR was a 12‐month prospective study of PUL in AUR patients (n = 51) performed at six centres in the United Kingdom; enrolled BPH patients aged ≥50 years, with prostate volume of ≤100 cc. AUR was defined as being catheter dependent with at least one prior failed trial without catheter (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“… 12 , 13 , 14 , 15 However, in the preoperative urinary retention group, the catheter‐free rates were reportedly 56% and 69% on postoperative days 3 and 5, respectively, and 71%–83% at 1 month postoperatively. 14 , 16 In our study, the overall catheter‐free rates were 82.0% and 92.0% on postoperative days 1 and 7, respectively, and 98.0% and 100% at 1 and 3 months postoperatively, respectively. The catheter‐free rates in the patients with preoperative nonurinary retention were 84.8% and 95.7% on postoperative days 1 and 7, respectively, and 100% at 1 month postoperatively.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“… 12 , 13 , 14 , 15 However, in the preoperative urinary retention group, the catheter‐free rates were reportedly 56% and 69% on postoperative days 3 and 5, respectively, and 71%–83% at 1 month postoperatively. 14 , 16 In our study, the overall catheter‐free rates were 82.0% and 92.0% on postoperative days 1 and 7, respectively, and 98.0% and 100% at 1 and 3 months postoperatively, respectively. The catheter‐free rates in the patients with preoperative nonurinary retention were 84.8% and 95.7% on postoperative days 1 and 7, respectively, and 100% at 1 month postoperatively.…”
Section: Discussionsupporting
confidence: 50%
“…This study suggests that many patients were older and had more comorbidities because of the insurance coverage of PUL in Japan; however, the initial outcomes revealed that it was safe and effective. Many reports from North America and Europe exist because they were early in introducing PUL, 12 , 13 , 14 , 15 , 16 , 17 , 18 whereas only limited reports are available from Asia, 10 as PUL was introduced a few years ago in this region. Although the number of patients in this study was small, three groups with different surgical techniques were examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation